The transformation of “Eco-Cop” as a Polri contingency strategy from policing in natural disaster perspective - Hasby Ristama (Privietlab, 2026)
This paper emphasizes the transformation of “Eco-Cop” as a Polri Contingency Strategy from policing in natural disasters perspective in the context of Indonesia today. Departing from the escalation of hydrometeorological disasters reflected in the 2025 Sumatra disaster, this study synthesizes four pillars, including green criminology, resilience policing, Incident Command System/Early Warning–Early Action (ICS/EWEA), and procedural justice as a prerequisite for public legitimacy. The methods used are in the form of policy and literature review combined with reading of the Polri operational cases in the emergency response phase, recovery transition, especially “green-wave” practices, heavy equipment pathfinding, and logistics lifeline security. The results of the synthesis show that the “Eco-Cop” operation can integrate weather/hydrological triggers into pre-closure decisions, pre-positioning, emergency contraflow, and priority escort of logistics lines. To ensure accountability and continuous improvement, this study proposes performance indicators, namely mean time to re-open (MTTR) of critical corridors, evacuation/logistics travel time, secondary incidents, coverage of reopened areas, and legitimacy/procedural justice index in crisis interactions. Policy implications include trigger-based cross-sector SOPs, integrated ICS/EWEA training, cross-agency operational data-sharing, and strengthening the humanitarian logistics interface (interoperability, digitalization, and greening standards). Overall, “Eco-Cop” in policing in natural disasters offers an adaptive, measurable, and equitable operating framework to reduce fatalities, accelerate recovery, and maintain community resilience in the midst of the climate crisis.